Persuasiveness in Political Discourse on Twitter - Olena Goroshko; Tetiana Poliakova (Психолінгвістика, 2018)
The article focuses on the question of new communication form appearance – the internet communication, namely political internet communication, that furthermore influenced the appearance of the new genres, among which we can find twitting. The active twitting usage with the communicative aim in political sphere puts the question about language learning namely about the means of expression of the persuasive language influence in the analyzed genre, as the persuasive language influence function is one of the most important functions in political internet-communication from psycholinguistic point of view.